Evaluating the application value of the modified Billroth-II with Braun anastomosis in laparoscopic distal gastric cancer radical surgery - Yubing Zhong; Yi Qian; Tao Wang (Journal of Minimal Access Surgery)
Introduction: This retrospective study aims to compare the feasibility and efficacy of the modified Billroth-II with Braun (B-II Braun) reconstruction with the Roux-en-Y (R-Y) reconstruction following laparoscopic distal gastrectomy. Patients and Methods: Between January 2020 and December 2022, 213 patients underwent total laparoscopic distal gastrectomy (TLDG). Of these, 125 patients underwent B-II Braun reconstruction and 8 underwent R-Y reconstruction. Patient data were prospectively collected and retrospectively analysed. Results: The modified B-II Braun reconstruction required shorter operative times compared to the R-Y approach (151.60 ± 12.50 vs. 182.50 ± 10.60; P = 0.0037), including anastomosis time (32.46 ± 1.55 vs. 48.80 ± 2.84; P = 0.016). At a 6-month short-term follow-up, endoscopic examination in the B-II Braun group revealed 27 cases of bile reflux and 15 cases (10.3%) of Grade 2 gastritis, with no cases of Grade 2 food residue. However, there was no statistically significant difference between the two groups in terms of food residue remaining in the residual stomach at 6 months (P = 0.29), gastritis at 6 months (P = 0.126) or bile reflux at 6 months (P = 0.209). Conclusion: For gastric cancer patients, TLDG with modified B-II Braun reconstruction is technically feasible. It offers an acceptable post-operative complication profile, shortens operative time, facilitates early post-operative recovery and effectively prevents bile reflux into the remnant stomach.